PENGARUH PERSEPSI SISW A TERHADAP PRESTASIBELAJAR DALAM MA TA PELAJARAN AKUNT ANSI :Penelitian Pada Siswa Kelas XI IPS SMA Pasundan 3 Bandung - Tina Siti Hasanah, - (2009)
This research derives from the student's result of testing which didn't satisfied. They got results below of Minimum Completeness Criteria (Kriteria Ketuntasan Minimum). Theoretically, many factors influenced student achievements, included internal and external factors. In order that, the purpose of this research is to reveal which factors can be influence to the student achievement of accountancy lesson in Pasundan 3 High School Bandung. The glaring factor which presume can influence the student's achievement is student perception of Accountancy Lesson. The research method use Explanatory Method And collect primer and secondary datas from questionairre, literary study, and documentary study. The population of this research is Pasundan 3 High School Bandung. The sampling technique use Simple Random Sampling, with 115 respondens. We use coefficient correlations analysis with SPSS 16 for windows to know the influence inter- variables. The result shows that correlation between independent and dependent variable are 0,825 which mean the correlation is very high. Variable of student perception have high impact to the student achievement, that is 68, 1 %. And the t test result is 15,538, that shows student perception have positive influence to the learning achievement of Accountancy Lesson. That mean if the students has good perception to the Accountancy Lesson, so it will increase they learning achievement. This research expect the role of Accountancy Lesson teacher to grant positive perception of Accountancy Lesson, so that influence positive reaction student to accountancy lesson, and can increase learning achievement.